2015
DOI: 10.14283/jpad.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Aspects of the Phase Ii Study Aff006 Evaluating Amyloid-Beta -Targeting Vaccine Affitope® Ad02 in Early Alzheimer’s Disease – Prospective Use of Novel Composite Scales

Abstract: BACKGROUND: Optimized scales and composite outcomes have been proposed as a way to more accurately measure Alzheimer’s disease related decline. AFFITOPE® AD02, is an amyloid-beta (Aβ)-targeting vaccine to elicit anti-Aβ antibodies. IMM-AD04, commonly known as Alum, originally designated as a control agent, appeared to have disease-modifying activity in a multicenter, parallel group phase II study in early AD patients. OBJECTIVES: To develop adapted outcomes for cognition, function and a composite scale with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Previous exposure to a range of vaccines (diphtheria, tetanus, poliomyelitis, influenza) was reported in 2001 to be associated with a 40% reduced risk of AD development [52]. More recently, in a Phase II trial of an AD vaccine, Affiris AG reported that administration of the adjuvant, alum, to control patients retarded AD-related cognitive decline across multiple measures [53,54]. Importantly, in a study of patients with bladder cancer, where BCG administration is the standard of care [55], the risk of developing AD was reported to be 4.8-fold lower in those receiving BCG than in untreated patients [56].…”
Section: Discussionmentioning
confidence: 99%
“…Previous exposure to a range of vaccines (diphtheria, tetanus, poliomyelitis, influenza) was reported in 2001 to be associated with a 40% reduced risk of AD development [52]. More recently, in a Phase II trial of an AD vaccine, Affiris AG reported that administration of the adjuvant, alum, to control patients retarded AD-related cognitive decline across multiple measures [53,54]. Importantly, in a study of patients with bladder cancer, where BCG administration is the standard of care [55], the risk of developing AD was reported to be 4.8-fold lower in those receiving BCG than in untreated patients [56].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, composite scores have often been derived to measure the most progressive aspects of disease, resulting in a decline that is as linear as possible in a specific disease stage ( 12 14 ). Commonly, these composite scores are weighted linear combinations of individual items from one or more clinical scales, where the weightings are determined by the magnitude of progression on each item, with faster progressing items receiving greater weight ( 13 ). If these composite scores are nearly linear, they approximate a perfect time metric.…”
Section: Methodsmentioning
confidence: 99%
“…The time savings assessed from individual scales can be combined across multiple outcomes into a single inference using a method similar to a global statistical test that accounts for correlations between outcomes and is referred to as a global TCT (gTCT) (1). Historically, composite scores were derived to measure the most progressive aspects of disease, resulting in a decline that is as linear as possible in a speci c disease stage (7)(8)(9). These composite scores are weighted linear combinations of individual items from one or more clinical scales, where the weightings are determined by the magnitude of progression on each item, with faster progressing items receiving greater weight (7).…”
Section: Tct Methodologymentioning
confidence: 99%
“…Each patient was randomly assigned to one of ve groups: 1 mg IMM-AD04, 2 mg IMM-AD04, 25 µg AD02 (in two different formulations) and 75 µg AD02 that also contained aluminum oxyhydroxide. The co-primary e cacy outcomes were the adapted ADAS-Cog (aADAS) and adapted Alzheimer's disease cooperative study activities of daily living scale (ADCS-ADL -aADL), which are optimized composite scales speci c to the cognitive and functional domains (9). A composite score (Composite) was the sum of these two scores, and this composite was the prespeci ed primary outcome of the study.…”
Section: Example Clinical Trialmentioning
confidence: 99%